2000
DOI: 10.1111/j.0435-3676.2000.00130.x
|View full text |Cite
|
Sign up to set email alerts
|

Geochronology of bonney drift, taylor valley, antarctica: evidence for interglacial expansions of taylor glacier

Abstract: Lacustrine algal carbonates, which form in shallow proglacial lakes, were found in most excavations into Bonney drift. Both in situ and reworked carbonate samples produced 49 new uranium/thorium (U/ Th) dates. U/Th dates of 70 to 130 ka for samples collected from excavations and natural sections, along with geomorphologic evidence reported elsewhere in this issue, confirm that the Bonney advance of Taylor Glacier, along with the concurrent expansion of local alpine glaciers, occurred during the interglaciation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 20 publications
1
30
0
Order By: Relevance
“…Stuiver et al () suggested that this water was initially “trapped” in the valley when sea level was lower, and then as sea level rose, seawater intruded from below. As noted above, advances and retreats of Taylor Glacier are well documented over time, and the lacustrine carbonates associated with proglacial lakes in what is now central Taylor Valley have δ 18 O formed from Taylor Glacier‐derived melt (Higgins et al, ). These advances of Taylor Glacier and the development of more eastward Taylor Glacier proglacial lakes occurred during Marine Isotopic stages 5a, 5c, 5e, 7, 9, and 11 (Higgins et al, ).…”
Section: Resultsmentioning
confidence: 97%
“…Stuiver et al () suggested that this water was initially “trapped” in the valley when sea level was lower, and then as sea level rose, seawater intruded from below. As noted above, advances and retreats of Taylor Glacier are well documented over time, and the lacustrine carbonates associated with proglacial lakes in what is now central Taylor Valley have δ 18 O formed from Taylor Glacier‐derived melt (Higgins et al, ). These advances of Taylor Glacier and the development of more eastward Taylor Glacier proglacial lakes occurred during Marine Isotopic stages 5a, 5c, 5e, 7, 9, and 11 (Higgins et al, ).…”
Section: Resultsmentioning
confidence: 97%
“…Utilizing published descriptions of the location, elevation and signature of preserved palaeoshorelines as a starting point, imagery derived from LiDAR coverages around known modern and ancient lake margins were scrutinized to visually identify preserved strandlines. In most cases, published literature provided the specific location of individual shorelines and provided evidence for a shoreline origin not easily attainable through remote-sensing techniques, including the presence of lacustrine algae and internal lithology (Clayton-Greene et al 1988;Butler 1999;Hall & Denton 1999, 2000Hendy 2000;Higgins et al 2000;Hall et al 2001Hall et al , 2004. Palaeoshorelines in the Dry Valleys region are characterized by 'step-andtread' cross-sectional profiles (Hendy 2000), distinct from the morphology of other glacial features.…”
Section: Methodsmentioning
confidence: 99%
“…Higgins et al 2000). While numerous lacustrine strandlines are preserved, identifying and correlating individual shoreline features in the LiDAR data is difficult owing to overprinting of features.…”
Section: Taylor Valleymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous investigations in Antarctica have examined lithified paleosols of late Paleozoic to early Triassic age (Retallack and Alonso-Zarza, 1998) and well-known exposures of semi-lithified paleosols of Miocene age (Retallack et al, 2002; Mahaney et al, 2001Mahaney et al, , 2012. Relict soils along the edge of the polar plateau throughout the TAMs have properties resulting from hyper-arid conditions, suggesting that the climate has remained cold and dry since the Miocene (Marchant et al, 1994).…”
Section: Introductionmentioning
confidence: 99%